The Psychology of Mountain People as a Subject of Special Research - Khrushch, Olena (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The article addresses the influence of natural and social-economic factors on the formation of the psychology of mountain people. A special mountain environment, living and housekeeping conditions, religious beliefs, and traditions mold stamina, pride, industriousness, and courage. The research into the psyche of Ukrainian mountain people living in the highest areas of Ivano-Frankivsk, Chernivtsi and Transcarpathian regions in the totalitarian period was openly scorned if not completely forbidden. For a long time, no research was done on the ethnic identity formation and rich feelings of hutsuls — a numerous ethnic community. Far too little attention was paid to hutsuls’ most important psychological traits of character — bravery, freedom of mind, dignity, respect for others, industriousness, stamina etc.